Hubungan Tingkat Pengetahuan Keluarga Tentang Demam Berdarah Dengan Motivasi Keluarga Terhadap Pencegahan Demam Berdarah - Moh Alimansur; Fajar Rinawati; Angga Pradityo (Akademi Keperawatan Dharma Husada Kediri, 2013)
Substantively dengue can be prevented and there won’t be any dengue occurrence if people understand about the danger of this disease. Family can take action to exterminate aedes aegypti mosquito by eradicating its larva, such as at puddle with three actions (3M); draining (spreading abate powder), closing water saving, and burying unused things which retain water. This research was a correlational research. The population in this research was family who lives at Sumberkepuh Area of Getas District, Subdistrict of Tanjunganom. The numbers of samples were 135 respondents. The sampling method was using simple random sampling. The result of the analysis was showing that the family knowledge level at Sumberkepuh Area of Getas District, Subdistrict of Tanjunganom mostly (52.5%) have fair knowledge. The family motivation levels at Sumberkepuh Area of Getas District, Subdistrict of Tanjunganom mostly (68%) have strong motivation. The score of Kendall’s tau between knowledge and motivation was 0.622. It means that there was a significant correlation between knowledge level and motivation level. It is need the participation of all family members to maintain health. Such as by doing three actions (3M); draining, closing, and burying.